Labour tax progressivity and output volatility: evidence from OECD countries - Maria-Grazia Attinasi; Cristina Checherita-Westphal; Malte Rieth (European Central Bank (ECB), 2011)
This paper investigates empirically the effect of personal income tax progressivity on output volatility in a sample of OECD countries over the period 1982-2009. Our measure of tax progressivity is based on the difference between the marginal and the average income tax rate for the average production worker. We find supportive empirical evidence for the hypothesis that higher personal income tax progressivity leads to lower output volatility. All other factors constant, countries with more progressive personal income tax systems seem to benefit from stronger automatic stabilisers.
Keywords: E63; E32; H10; 330; automatic stabilisers; output volatility; personal income taxes; Progressivity